Method for producing separation membrane and separation membrane produced using same
By controlling the stretching ratio and heat setting process of the polyolefin substrate and combining it with inorganic particle coating, the problems of high thermal shrinkage and insufficient permeability of ultra-high molecular weight polyethylene separation membranes were solved, thereby improving the performance of lithium secondary batteries.
Patent Information
- Application Number
- CN202480017920.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-05-16
- Filing Date
- 2024-02-20
- Publication Date
- 2025-10-24
AI Technical Summary
In the prior art, ultra-high molecular weight polyethylene separation membranes have problems of high thermal shrinkage and low mechanical strength during processing, and the ceramic coating separation membranes have insufficient air permeability, which affects the charge and discharge performance of lithium secondary batteries.
A substrate is made of a composition of polyolefin and a pore-forming agent, which is stretched longitudinally and transversely and heat-set to control the stretching ratio to meet specific conditions to form a porous membrane, and a functional layer is coated on the surface of the porous membrane, including a coating solution of inorganic particles and an adhesive.
A balance among heat resistance, mechanical strength and gas permeability of the separation membrane is achieved, thereby improving the battery life and charge and discharge performance of the lithium secondary battery.
Smart Images

Figure BDA0005587807880000131 
Figure BDA0005587807880000161 
Figure BDA0005587807880000171
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to a manufacturing method of a separation membrane and a separation membrane manufactured using the same. BACKGROUND
[0002] Lithium secondary batteries are widely used as power sources for various electronic products such as smartphones, notebook computers, and tablet computers that require miniaturization and light weight, and as the application fields thereof are expanded to smart grids and medium-to-large batteries for electric vehicles, there is a need to develop lithium secondary batteries having large capacity, long life, and high stability.
[0003] In recent years, in order to improve the capacity of lithium secondary batteries, thinning of a separation membrane has become a technical issue. However, such thinning is accompanied by a decrease in mechanical strength, and thus it is necessary to achieve a balance between the two. For this reason, separation membranes using a resin having a higher weight average molecular weight than general-purpose polyethylene, such as a separation membrane using ultra-high molecular weight polyethylene (UHMWPE), are being continuously developed.
[0004] Ultra-high molecular weight polyethylene (UHMWPE) generally refers to polyethylene having a weight average molecular weight of 1,000,000 or more. According to Japanese Laid-Open Patent No. 60-242035 or the like, ultra-high molecular weight polyethylene has excellent properties in terms of mechanical strength, wear resistance, uniformity, self-lubricity, and chemical resistance, compared to general-purpose polyethylene such as high-density polyethylene and low-density polyethylene.
[0005] However, ultra-high molecular weight polyethylene has low flowability even in a completely molten state due to its high molecular weight, resulting in processing difficulties, and there are problems such as a decrease in heat resistance of the manufactured separation membrane in terms of thermal shrinkage at high temperatures (150°C).
[0006] On the other hand, in order to improve the heat resistance of the separation membrane, a separation membrane in which ceramic particles are coated on the surface of a porous support, i.e., a so-called ceramic-coated separation membrane, has been proposed. However, the above-described ceramic-coated separation membrane has considerable technical issues in terms of air permeability. That is, when a heat-resistant layer containing ceramic particles is coated on the surface of the above-described porous support, the heat resistance of the separation membrane is improved, but the above-described heat-resistant layer closes the pores formed in the above-described porous support, thereby decreasing the air permeability of the separation membrane, and thus the ion movement path between the positive electrode and the negative electrode is reduced, and as a result, there is a problem in that the charge and discharge properties of the battery are greatly reduced.
[0007] Attempts have been made to improve the adhesion to the electrode and extend the life of the battery by additionally forming an adhesion layer having adhesion to the electrode on the surface of the above-described porous support and / or the surface of the above-described heat-resistant layer.
[0008] A separation membrane coated with a functional layer such as a heat-resistant layer or an adhesion layer is generally manufactured by coating and drying a composition for forming the functional layer on one side or both sides of a porous support body traveling at a constant speed while the porous support body is traveling at a constant speed. However, when the porous support body includes or is made of ultra-high molecular weight polyethylene, there is a problem that the thermal shrinkage rate of the porous support body is further increased due to heat applied to the separation membrane in a drying process for forming the functional layer. SUMMARY
[0009] TECHNICAL PROBLEM
[0010] The present application aims to solve the above-described problems of the prior art, and an object of the present application is to provide a manufacturing method of a separation membrane capable of achieving and improving processability, heat resistance, and puncture strength in balance, and a separation membrane manufactured using the same.
[0011] SOLUTION TO THE PROBLEM
[0012] One aspect of the present application provides a manufacturing method of a separation membrane, the manufacturing method of the separation membrane including: step (a) of processing a composition including a polyolefin and a pore former to obtain a base sheet; step (b) of stretching the base sheet in a machine direction (MD) and a transverse direction (TD) and removing the pore former to obtain a porous membrane; and step (c) of stretching and heat-setting the porous membrane in the transverse direction (TD); the manufacturing method of the separation membrane satisfying conditions (1) to (3) below:
[0013] (1) 7 ≤ Mb ≤ 8, (2) 0 < Mb / Tb < 1, (3) 0 < Mb / (Tb × Tc) < 0.5.
[0014] In the above (1) to (3), Mb and Tb are the stretching ratios of the base sheet in the machine direction (MD) and the transverse direction (TD) in the step (b), and Tc is the stretching ratio of the porous membrane in the transverse direction (TD) in the step (c).
[0015] In one embodiment, the polyolefin can have a weight average molecular weight (Mw) of 1,000,000 to 4,000,000.
[0016] In one embodiment, the polyolefin can include one selected from the group consisting of polyethylene, polypropylene, polybutylene, polymethylpentene, ethylene vinyl acetate, ethylene butyl acrylate, ethylene ethyl acrylate, and a combination or copolymer of two or more thereof.
[0017] In one embodiment, the Tc can be 1.5 to 2.0.
[0018] In one embodiment, the ratio of the Mb to the Tc (Mb / Tc) can be 3.0 to 5.0.
[0019] In one embodiment, the pore forming agent described above can be a paraffin oil having a kinematic viscosity of 50 cSt to 100 cSt at 40°C, respectively.
[0020] In one embodiment, the thickness of the substrate obtained in the step (a) described above can be 1000 μm to 1500 μm, and the thickness of the porous membrane obtained in the step (c) described above can be 10 μm or less, and the puncture strength can be 500 gf or more.
[0021] In one embodiment, the method of manufacturing the separation membrane further includes a step (d) of applying a coating solution containing a binder and a solvent to at least one side of the porous membrane and drying to form a functional layer after the step (c) described above.
[0022] In one embodiment, the binder can be one selected from the group consisting of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride-trichloroethylene, polymethyl methacrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinyl acetate, ethylene vinyl acetate, polyimide, polyethylene oxide, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, hydroxyethyl cellulose, cyanoethyl sucrose, pullulan, carboxymethyl cellulose, polyvinyl alcohol, polyvinyl butyral, acrylonitrile-acrylic acid copolymer, ethylene-acrylic acid copolymer, styrene-butadiene copolymer, alkyl acrylate-acrylonitrile copolymer, polyethylene glycol, acrylic rubber, and a combination of two or more thereof.
[0023] In one embodiment, the solvent can be one selected from the group consisting of methanol, ethanol, propanol, butanol, methoxyethanol, ethoxyethanol, lactone, acetonitrile, n-methyl-2-pyrrolidone, formic acid, nitromethane, acetic acid, dimethyl sulfoxide, water, and a combination of two or more thereof.
[0024] In one embodiment, the coating solution can further include one inorganic particle selected from the group consisting of SiO2, AlO(OH), Mg(OH)2, Al(OH)3, TiO2, BaTiO3, Li2O, LiF, LiOH, Li3N, BaO, Na2O, Li2CO3, CaCO3, LiAlO2, Al2O3, SiO, SnO, SnO2, PbO2, ZnO, P2O5, CuO, MoO, V2O5, B2O3, Si3N4, CeO2, Mn3O4, Sn2P2O7, Sn2B2O5, Sn2BPO6, and a combination of two or more thereof.
[0025] Another aspect of the present application provides a separation membrane, the separation membrane being a separation membrane produced by the production method of a separation membrane described above, the separation membrane satisfying the following conditions (i) to (iii):
[0026] (i) a longitudinal (MD) heat shrinkage at 150°C of 5% or less, (ii) a transverse (TD) heat shrinkage at 150°C of 5% or less, and (iii) a ratio of the transverse (TD) heat shrinkage to the longitudinal (MD) heat shrinkage at 150°C of 1.1 or less.
[0027] Effects of the Invention
[0028] The production method of a separation membrane according to an aspect of the present application includes: step (a) of processing a composition containing a polyolefin and a pore-forming agent to obtain a base sheet; step (b) of stretching the base sheet in the longitudinal (MD) and transverse (TD) directions and removing the pore-forming agent to obtain a porous membrane; and step (c) of stretching and heat-setting the porous membrane in the transverse (TD) direction, and satisfying the following conditions (1) to (3), so that processability, heat resistance, and puncture strength can be balanced and improved.
[0029] (1) 7 < Mb < 8, (2) 0 < Mb / Tb < 1, and (3) 0 < Mb / (Tb x Tc) < 0.5.
[0030] In the above (1) to (3), Mb and Tb are the stretching ratios of the base sheet in the longitudinal (MD) and transverse (TD) directions in step (b) described above, respectively, and Tc is the stretching ratio of the porous membrane in the transverse (TD) direction in step (c) described above.
[0031] The effects of the present application are not limited to the above-mentioned effects, and it should be understood that all effects that can be inferred from the configuration of the application described in the detailed description or claims are included. DETAILED DESCRIPTION
[0032] Hereinafter, the present application will be described. However, the present application can be implemented in various different forms, and is not limited to the embodiments described in this specification.
[0033] Throughout this specification, when a component is described as "connected to" another component, it includes not only a case where the component is "directly connected" to the other component, but also a case where the component is "connected to" the other component with other components interposed therebetween. In addition, when a part is referred to as "including" or "comprising" an element, unless otherwise specified, it can mean that the part can further include another element, instead of excluding any other element.
[0034] One aspect of the present application provides a method for producing a separation membrane, the method for producing a separation membrane comprising: step (a) of processing a composition comprising a polyolefin and a pore former to obtain a base sheet; step (b) of stretching the base sheet in a machine direction (MD) and a transverse direction (TD) and removing the pore former to obtain a porous membrane; and step (c) of stretching the porous membrane in the transverse direction (TD) and heat setting; the method for producing a separation membrane satisfying conditions (1) to (3) below:
[0035] (1) 7 ≤ Mb ≤ 8, (2) 0 < Mb / Tb < 1, (3) 0 < Mb / (Tb × Tc) < 0.5.
[0036] In the above (1) to (3), Mb and Tb are the stretching ratios of the base sheet in the machine direction (MD) and the transverse direction (TD) in the above step (b), respectively, and Tc is the stretching ratio of the porous membrane in the transverse direction (TD) in the above step (c).
[0037] In the above step (a), the composition comprising a polyolefin and a pore former can be extruded and discharged through a T-die to obtain a base sheet. The weight average molecular weight (Mw) of the polyolefin can be 1,000,000 to 4,000,000, preferably, can be 1,500,000 to 3,000,000, more preferably, can be 1,500,000 to 2,500,000, and the molecular weight distribution (Mw / Mn) can be 3 to 7. If the weight average molecular weight of the polyolefin is less than 1,000,000, the mechanical strength of the separation membrane can be reduced, and if the weight average molecular weight of the polyolefin exceeds 4,000,000, the heat shrinkage can be excessively increased, resulting in reduced heat resistance. In addition, if the molecular weight distribution of the polyolefin is less than 3, the dispersibility of the pore former is reduced, and thus the uniformity of the produced separation membrane can be reduced, and if the molecular weight distribution of the polyolefin is greater than 7, the mechanical properties of the separation membrane can be reduced. The terms "weight average molecular weight" and "molecular weight distribution" used in the present specification mean values measured by gel permeation chromatography (GPC) using polystyrene as a standard sample according to the method described in the literature (Macromolecules, Vol. 34, No. 19, pp. 6812-6820 (2001) or the like).
[0038] The polyolefin can include one selected from the group consisting of polyethylene, polypropylene, polybutylene, polymethylpentene, ethylene vinyl acetate, ethylene butyl acrylate, ethylene ethyl acrylate, and a combination or copolymer of two or more thereof, preferably, can include polyethylene and / or polypropylene, more preferably, can include polyethylene, but is not limited thereto.
[0039] The pore forming agent can be one selected from the group consisting of paraffin oil, paraffin wax, mineral oil, solid paraffin wax, soybean oil, rapeseed oil, palm oil, coconut oil, di-2-ethylhexyl phthalate, dibutyl phthalate, diisononyl phthalate, diisodecyl phthalate, di(2-propylheptyl) phthalate, naphthenic oil, and combinations of two or more thereof, preferably, paraffin oil, more preferably, paraffin oil having a kinematic viscosity of 50 cSt to 100 cSt at 40°C, but is not limited thereto. The composition can include 10 to 50 wt% of the polyolefin and 50 to 90 wt% of the pore forming agent, preferably, 20 to 40 wt% of the polyolefin and 60 to 80 wt% of the pore forming agent.
[0040] The thickness of the substrate obtained in step (a) can be 1,000 to 1,500 μm, preferably, 1,200 to 1,500 μm. If the composition contains an ultra-high molecular weight polyolefin, for example, ultra-high molecular weight polyethylene having a weight average molecular weight of 2,000,000 or more, it is difficult to control the thickness of the substrate to be less than 1,000 μm by extrusion or casting, and if the thickness of the substrate exceeds 1,500 μm, there is a problem that it is difficult to make the separation membrane thin even by subsequent stretching.
[0041] In step (b), the substrate can be stretched in the machine direction (MD) and the transverse direction (TD) and the pore forming agent can be removed, thereby obtaining a porous membrane. The stretching can be achieved by biaxial stretching in the order of stretching the substrate first in the machine direction (MD) and then in the transverse direction (TD) at a predetermined stretching ratio, or by simultaneous biaxial stretching by stretching in the machine direction (MD) and the transverse direction (TD) at the same time. The term "stretching ratio" used in the present specification means the ratio of the length in the machine direction (MD) or the transverse direction (TD) after stretching to the length in the machine direction (MD) or the transverse direction (TD) of the substrate before stretching, and can be understood to have the same meaning as stretch ratio, stretch rate, etc.
[0042] The stretching of the substrate in the machine direction (MD) can be achieved by a roll-type stretching machine. The roll-type stretching machine is a device that stretches the substrate in the direction of the substrate transport in the process line, and the direction in which the substrate is stretched by the roll-type stretching machine can be defined as the machine direction (MD, mechanical direction). The roll-type stretching machine includes a plurality of rollers arranged in the direction of the substrate transport, and can stretch the substrate in the machine direction at a predetermined ratio by rotating the rear roller faster than the front roller.
[0043] The transverse (TD) stretching of the substrate can be performed by a tenter stretcher. The tenter stretcher is a device that stretches the substrate in a direction perpendicular to the substrate transport direction in a process line, and separates the members that fix the both ends of the substrate in the transverse direction by using a jig, a clamp, or the like, thereby stretching the substrate in the transverse direction at a predetermined stretch ratio.
[0044] The pore-forming agent can be selectively extracted and removed from the substrate by applying a specific extraction solvent to the substrate. A solution containing the extraction solvent can be loaded into a dip tank, and the substrate can be immersed in the solution for a predetermined time, thereby extracting and removing the pore-forming agent.
[0045] The amount of the pore-forming agent remaining on the surface and / or inside of the porous membrane after extraction can be 1% by weight or less. For example, the extraction solvent can be methyl ethyl ketone, hexane, dichloromethane, or the like, but is not limited thereto. The time required for extraction and removal of the pore-forming agent can be determined according to the thickness and / or porosity of the substrate and / or the porous membrane, but in the case where the thickness and porosity of the porous membrane are 1 μm to 10 μm and 30% by volume to 70% by volume, respectively, the time can be 10 minutes or less, preferably 5 minutes or less.
[0046] In addition, the extraction solvent remaining in the porous membrane can be removed by heating the porous membrane from which the pore-forming agent has been extracted and removed. A portion of the extraction solvent applied in step (b) can remain on the surface and / or inside of the porous membrane. Since the remaining extraction solvent can adversely affect subsequent processes and the physical properties of a separation membrane produced by the processes, the porous membrane can be heated to a temperature higher than the boiling point of the extraction solvent to remove the extraction solvent remaining in the porous membrane.
[0047] In step (c), a separation membrane is obtained by stretching the porous membrane in the transverse (TD) direction and heat setting.
[0048] The heat setting refers to a process of applying heat to the porous membrane stretched in the transverse (TD) direction in a state of being relaxed and fixed, to forcibly fix the porous membrane that is to be shrunk, thereby eliminating residual stress. Although a high heat setting temperature is advantageous in reducing the thermal shrinkage of the separation membrane, if the temperature is too high, the porous membrane can be locally melted, thereby causing the formed pores to be closed, resulting in a decrease in air permeability.
[0049] The heat setting temperature is preferably selected in a range of 10 to 30% by weight of the crystalline portion of the above porous membrane being melted. When the heat setting temperature is selected in the above range, the problem of no residual stress relief effect due to insufficient rearrangement of the polyolefin molecules within the above porous membrane and the problem of the porosity being closed and the air permeability being reduced due to partial melting can be prevented. For example, the heat setting temperature can be 120 to 140°C, preferably, 123 to 135°C, and the heat setting time can be 5 seconds to 1 minute.
[0050] As to the above stretching performed in the above step (b) and step (c), the above production method of the separation membrane can satisfy the following conditions (1) to (3).
[0051] (1) 7 < Mb < 8, (2) 0 < Mb / Tb < 1, (3) 0 < Mb / (Tb x Tc) < 0.5.
[0052] In the above (1) to (3), Mb and Tb are the stretching ratios of the above base sheet in the longitudinal direction (MD) and the transverse direction (TD) in the above step (b), respectively, and Tc is the stretching ratio of the above porous membrane in the transverse direction (TD) in the above step (c).
[0053] The above condition (1) relates to the stretching ratio (Mb) of the above base sheet in the longitudinal direction (MD) in the above step (b), and the above Mb can be 7 to 8, preferably, 7 to 7.5. When the above Mb is less than 7, the structural properties required for the above porous membrane, such as the pore diameter, the porosity, and the air permeability, can be reduced, and when the above Mb is more than 8, the heat shrinkage of the separation membrane in the longitudinal direction (MD) can be increased, thereby reducing the heat resistance. In particular, when the above Mb is adjusted to the predetermined range, it can be understood that the above base sheet is relatively and substantially shrunk in the transverse direction (TD) in the state of being stretched in the longitudinal direction (MD), and this shrinkage can alleviate the residual stress accumulated in the above base sheet and / or the above porous membrane by the subsequent stretching in the transverse direction (TD), thereby contributing to the reduction of the heat shrinkage of the separation membrane and the improvement of the heat resistance thereof. In addition, if the heat resistance of the above porous membrane is improved, the resistance to heat applied to the above porous membrane during the coating and drying processes of forming a functional layer on the surface of the above porous membrane is also improved, thereby preventing the separation membrane from being arbitrarily deformed and / or denatured.
[0054] The condition (2) above relates to the ratio of the stretch ratio in the machine direction (MD) in the above step (b) to the stretch ratio of the base sheet in the transverse direction (TD), which can be greater than 0 and less than 1, preferably 0.5 to 0.95, more preferably 0.7 to 0.9. Here, the Tb can be 8.0 to 10.0, preferably 8.5 to 9.5. The Tb is the stretch ratio in the transverse direction (TD) during the biaxial stretching in the above step (b). By controlling the Tb to be less than the Mb, the residual stress accumulated in the base sheet can be relaxed by the transverse direction (TD) stretching during the biaxial stretching, thereby contributing to the reduction of the heat shrinkage of the separation membrane and the improvement of the heat resistance. Further, if the Tb is less than 0.5, the required structural properties of the porous membrane, such as the pore diameter, the porosity, the orientation of the pores, the air permeability, and the like, can be reduced.
[0055] The condition (3) above relates to the ratio between the stretch ratio of the base sheet in the machine direction (MD) in the above step (b) and the total stretch ratio in the transverse direction (TD) during the entire process of manufacturing the separation membrane, which can be greater than 0 and less than 0.5, preferably 0.3 or more, more preferably 0.4 or more. Here, the Tc can be 1.5 to 2.0, preferably 1.7 to 1.9. When the Mb / (Tb x Tc) is greater than or equal to 0.5, the heat shrinkage in the machine direction (MD) and the heat shrinkage in the transverse direction (TD) of the separation membrane will both increase, and in particular, the heat shrinkage in the transverse direction (TD) will sharply increase, thereby leading to the reduction of the heat resistance.
[0056] The ratio (Mb / Tc) of the stretch ratio of the base sheet in the machine direction (MD) in the above step (b) to the stretch ratio of the porous membrane in the transverse direction (TD) in the above step (c) can be 3.0 to 5.0, preferably 3.5 to 4.8, more preferably 3.5 to 4.5, but is not limited thereto.
[0057] The thickness of the porous membrane obtained in the above step (c) can be 10 μm or less, preferably, 1 μm to 8 μm, more preferably, 2 μm to 7 μm. If the thickness of the porous membrane exceeds 10 μm, it is difficult to make the separation membrane thin, and it is difficult to make the battery including the separation membrane small and integrated, and if the thickness of the porous membrane is less than 1 μm, the mechanical strength of the separation membrane, in particular, the puncture strength can be reduced. The puncture strength of the porous membrane obtained in the above step (c) can be 500 gf or more, preferably 500 gf to 1000 gf, more preferably 510 gf to 800 gf.
[0058] The separation membrane obtained in the above step (c) can be directly used in the battery assembly, and if necessary, it can be used after forming a functional layer described later on the surface thereof.
[0059] The step (c) can be followed by a step (d) of applying a coating solution containing a binder and a solvent to at least one side of the porous membrane and drying to form a functional layer. Specifically, in the step (d), a coating solution containing a binder and a solvent can be applied to at least one side of the porous membrane and dried, thereby removing the solvent and other liquid residues contained in the coating solution to form a functional layer. The functional layer can be formed on one side of the porous membrane, or on both sides if necessary. The functional layers formed on both sides of the porous membrane can have the same thickness, composition, and effects, or at least one of them can be different depending on the circumstances.
[0060] The binder can be one selected from the group consisting of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride-trichloroethylene, polymethyl methacrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinyl acetate, ethylene vinyl acetate, polyimide, polyethylene oxide, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, hydroxyethyl cellulose, cyanoethyl sucrose, pullulan, carboxymethyl cellulose, polyvinyl alcohol, polyvinyl butyral, acrylonitrile-acrylic acid copolymer, ethylene-acrylic acid copolymer, styrene-butadiene copolymer, alkyl acrylate-acrylonitrile copolymer, polyethylene glycol, acrylic rubber, and combinations of two or more of them, preferably carboxymethyl cellulose and alkyl acrylate-acrylonitrile copolymer, but not limited thereto. For example, in the functional layer, the carboxymethyl cellulose and the alkyl acrylate-acrylonitrile copolymer can be present in a weight ratio of 1:0.5 to 1.5, respectively.
[0061] The coating solution can further include inorganic particles selected from the group consisting of SiO2, AlO(OH), Mg(OH)2, Al(OH)3, TiO2, BaTiO3, Li2O, LiF, LiOH, Li3N, BaO, Na2O, Li2CO3, CaCO3, LiAlO2, Al2O3, SiO, SnO, SnO2, PbO2, ZnO, P2O5, CuO, MoO, V2O5, B2O3, Si3N4, CeO2, Mn3O4, Sn2P2O7, Sn2B2O5, Sn2BPO6, and combinations of two or more of them, which can help improve the heat resistance of the functional layer and the separation membrane. Preferably, the inorganic particles can be Al2O3 and / or AlO(OH), but not limited thereto.
[0062] The content of the inorganic particles in the functional layer can be 50 to 95% by weight. If the content of the inorganic particles in the functional layer is less than 50% by weight, the desired level of heat resistance cannot be imparted, and if the content of the inorganic particles in the functional layer is more than 95% by weight, the dispersibility of the inorganic particles can be reduced, or the coatability and processability of the coating layer can be reduced.
[0063] The inorganic particles tend to agglomerate by electrostatic attraction. The aggregation of these inorganic particles can reduce the uniformity of the physical properties of the surface of the separation membrane. In this regard, the coating solution can further include an additive for improving the dispersibility of the inorganic particles, for example, can further include a dispersant, a surfactant, or the like. In particular, the coating solution can include sodium hexametaphosphate ((NaPO3)6) as a dispersant, and the content of the sodium hexametaphosphate in the functional layer can be 0.01 to 1% by weight, preferably, 0.01 to 0.5% by weight. The sodium hexametaphosphate is adsorbed on the edge portion of the inorganic particles, particularly the edge portion of the plate-shaped inorganic particles, to weaken the negative (-) charge of the edge portion, effectively preventing the aggregation of the inorganic particles, thereby improving the storage stability of the coating solution for forming the functional layer and the dispersibility of the inorganic particles in the functional layer.
[0064] To prepare a water-soluble coating solution, the solvent can be one selected from the group consisting of methanol, ethanol, propanol, butanol, methoxyethanol, ethoxyethanol, lactone, acetonitrile, n-methyl-2-pyrrolidone, formic acid, nitromethane, acetic acid, dimethyl sulfoxide, water, and a combination of two or more thereof, preferably, can be ethanol and water, more preferably, can be a mixture in which ethanol and water are each mixed at a weight ratio of 1:10 to 1:50, but is not limited thereto.
[0065] The coating solution can include 30 to 100 parts by weight of inorganic particles and 1 to 20 parts by weight of a binder based on 100 parts by weight of the solvent, and preferably, can be water-soluble (aqueous or water-based). In consideration of the balance between processability, coatability, and heat resistance, the content of solids in the coating solution can be adjusted to 20 to 50% by weight, preferably, 30 to 40% by weight.
[0066] The thickness of the functional layer can be 1 to 10 μm. If the thickness of the functional layer is less than 1 μm, the desired level of adhesion and heat resistance cannot be imparted, and if the thickness of the functional layer is more than 10 μm, the separation membrane becomes thick, which can hinder the high capacity, miniaturization, and integration of batteries or elements.
[0067] On the other hand, before the above coating solution is coated on both sides of the above porous membrane in the above step (d), the above porous membrane can be subjected to plasma treatment in the presence of a mixed gas containing sulfur dioxide (SO2) and oxygen (O2).
[0068] Through the above plasma treatment, the surface of the above porous membrane and / or the surface of the internal pores can be hydrophilized, thereby improving the binding force between both sides of the above porous membrane and the above coating solution, and thus the durability of the separation membrane, particularly long-term durability and heat resistance, can be significantly improved.
[0069] In the past, in order to hydrophilize the surface of the porous membrane, a wet process of impregnating in sulfuric acid or the like for a certain period of time to sulfonate has been mainly used, but in this case, the above wet process is performed separately from the above plasma treatment, for example, before or after the plasma treatment, and thus there is a problem that the process is complicated and a large amount of process waste liquid is generated.
[0070] In this regard, since the process gas used in the above plasma treatment includes existing air, oxygen and / or inert gas and a certain amount of sulfur dioxide gas, through the above plasma treatment which is a single dry process in addition to the wet process of impregnating the porous membrane in sulfuric acid or the like, a functional group such as -SO3 is generated on the surface of the porous membrane and the surface of the internal pores, i.e., sulfonation is performed, and thus the hydrophilicity and ionic conductivity of the porous membrane can be maximized, the existing complicated process can be simplified, and it is also environmentally advantageous.
[0071] The above mixed gas used in the above plasma treatment can include 50 to 90% by volume of sulfur dioxide and 10 to 50% by volume of oxygen, preferably, 60 to 80% by volume of sulfur dioxide and 20 to 40% by volume of oxygen, and more preferably, 70 to 80% by volume of sulfur dioxide and 20 to 30% by volume of oxygen. If the content of sulfur dioxide in the above mixed gas is less than 50% by volume, the required level of hydrophilicity of the above porous membrane can not be achieved, and if the content of sulfur dioxide in the above mixed gas is greater than 90% by volume, the process can be unstable.
[0072] The above plasma treatment can be performed for 0.5 to 90 minutes, and preferably, for 0.5 to 20 minutes. If the above plasma treatment time is less than 0.5 minutes, the above porous membrane cannot be hydrophilized or sulfonated to the required level, and if the above plasma treatment time is greater than 90 minutes, the degree of hydrophilization and sulfonation converges to a certain level, and thus the process efficiency can be reduced.
[0073] The separation membrane manufactured using the manufacturing method of the separation membrane described above can satisfy the following conditions (i) to (iii).
[0074] (i) a longitudinal (MD) heat shrinkage of 5% or less, preferably 1.0 to 4.5%, more preferably 1.9 to 4.0% at 150°C; (ii) a transverse (TD) heat shrinkage of 5% or less, preferably 1.0 to 4.8%, more preferably 1.5 to 4.0% at 150°C; and (iii) a ratio of the transverse (TD) heat shrinkage to the longitudinal (MD) heat shrinkage of 1.1 or less, preferably 0.5 to 1.0, more preferably 0.6 to 0.9 at 150°C.
[0075] Hereinafter, embodiments of the present application will be described in more detail.
[0076] Example 1
[0077] A mixture of 20 parts by weight of ultra-high molecular weight polyethylene (UHMWPE) having a weight average molecular weight (Mw) of 2,000,000 and a molecular weight distribution (Mw / Mn) of 5 and 80 parts by weight of paraffin oil having a kinematic viscosity of 70 cSt at 40°C was introduced into a twin-screw extruder (inner diameter: 58 mm, L / D = 56). The mixture was discharged from the twin-screw extruder to a T-die having a width of 630 mm under the conditions of a screw rotation speed of 40 rpm and a temperature of 200°C, and then passed through a casting roll having a temperature of 17°C, thereby manufacturing a base sheet having a thickness of 1,450 μm.
[0078] The above base sheet was stretched 8.0 times in the longitudinal direction (MDO process) at 105°C using a roll stretcher, and then stretched 9.5 times in the transverse direction (TD01 process) at 125°C using a tension stretcher, and then immersed in a methylene chloride immersion tank at 25°C for 1 minute to extract and remove the paraffin oil, and then dried at 50°C for 5 minutes, thereby manufacturing a porous membrane. The above porous membrane was stretched 1.7 times in the transverse direction (TD02 process) at 134°C, and heat-set in a relaxed state of 18%, thereby manufacturing a first separation membrane having a thickness of 7 μm.
[0079] The following Table 1 was mixed at a ratio to prepare a water-dispersed ceramic slurry, and then dispersed using a ball mill.
[0080] Table 1
[0081]
[0082] A second separation film including a functional layer (heat resistant layer) having a thickness of 3 μm was obtained by applying the above water-dispersed ceramic slurry to one side of the above first separation film, concave coating with a 110-mesh coating roll, and drying in a wind oven at a temperature of 80°C for 1 hour.
[0083] Example 2
[0084] A first separation film and a second separation film were produced in the same manner as in the above Example 1, except that the above substrate was stretched 7.5 times in the longitudinal direction (MD) in the above MDO process.
[0085] Example 3
[0086] A first separation film and a second separation film were produced in the same manner as in the above Example 1, except that the above substrate was stretched 7.0 times in the longitudinal direction (MD) in the above MDO process.
[0087] Example 4
[0088] A first separation film and a second separation film were produced in the same manner as in the above Example 1, except that the above substrate was stretched 8.5 times in the transverse direction (TD) in the above TDOl process and the above porous film was stretched 2.0 times in the transverse direction (TD) in the above TDO2 process.
[0089] Example 5
[0090] A first separation film and a second separation film were produced in the same manner as in the above Example 4, except that the above substrate was stretched 7.5 times in the longitudinal direction (MD) in the above MDO process.
[0091] Example 6
[0092] A first separation film and a second separation film were produced in the same manner as in the above Example 4, except that the above substrate was stretched 7.0 times in the longitudinal direction (MD) in the above MDO process.
[0093] Example 7
[0094] A first separation film and a second separation film were produced in the same manner as in the above Example 1, except that the above substrate was stretched 8.5 times in the transverse direction (TD) in the above TDOl process and the above porous film was stretched 2.0 times in the transverse direction (TD) in the above TDO2 process.
[0095] Example 8
[0096] The first separation membrane and the second separation membrane were prepared in the same manner as in Example 7, except that the above-mentioned substrate was stretched 7.5 times in the longitudinal direction (MD) in the above-mentioned MDO process.
[0097] Example 9
[0098] The first separation membrane and the second separation membrane were prepared in the same manner as in Example 7, except that the above-mentioned substrate was stretched 7.0 times in the longitudinal direction (MD) in the above-mentioned MDO process.
[0099] Comparative Example 1
[0100] The first separation membrane and the second separation membrane were prepared in the same manner as in Example 4, except that the above-mentioned substrate was stretched 9.0 times in the longitudinal direction (MD) in the above-mentioned MDO process.
[0101] Comparative Example 2
[0102] The first separation membrane and the second separation membrane were prepared in the same manner as in Comparative Example 1, except that the above-mentioned substrate was stretched 8.5 times in the transverse direction (TD) in the above-mentioned TDOl process.
[0103] Comparative Example 3
[0104] The first separation membrane and the second separation membrane were prepared in the same manner as in Comparative Example 1, except that the above-mentioned substrate was stretched 8.0 times in the transverse direction (TD) in the above-mentioned TDOl process.
[0105] Comparative Example 4
[0106] The first separation membrane and the second separation membrane were prepared in the same manner as in Comparative Example 1, except that the above-mentioned porous membrane was stretched 2.0 times in the transverse direction (TD) in the above-mentioned TDO2 process.
[0107] Comparative Example 5
[0108] The first separation membrane and the second separation membrane were prepared in the same manner as in Comparative Example 1, except that the above-mentioned porous membrane was stretched 1.7 times in the transverse direction (TD) in the above-mentioned TDO2 process.
[0109] Comparative Example 6
[0110] The first separation membrane and the second separation membrane were prepared in the same manner as in Comparative Example 1, except that the above-mentioned porous membrane was stretched 1.5 times in the transverse direction (TD) in the above-mentioned TDO2 process.
[0111] Comparative Example 7
[0112] A first separation membrane and a second separation membrane were prepared in the same manner as in the above Comparative Example 1, except that the above porous membrane was stretched 1.8 times in the transverse direction (TD) in the above TDO2 process.
[0113] Comparative Example 8
[0114] A first separation membrane and a second separation membrane were prepared in the same manner as in the above Comparative Example 7, except that the above substrate was stretched 8.5 times in the machine direction (MD) in the above MDO process.
[0115] Comparative Example 9
[0116] A first separation membrane and a second separation membrane were prepared in the same manner as in the above Comparative Example 7, except that the above substrate was stretched 8.3 times in the machine direction (MD) in the above MDO process.
[0117] Comparative Example 10
[0118] A first separation membrane and a second separation membrane were prepared in the same manner as in the above Example 1, except that 20 parts by weight of ultra high molecular weight polyethylene (UHMWPE) having a weight average molecular weight (Mw) of 2,000,000 and a molecular weight distribution (Mw / Mn) of 5 and 80 parts by weight of paraffin oil having a kinematic viscosity of 70 cSt at 40°C were mixed and fed into a twin-screw extruder (inner diameter: 58 mm, L / D = 56), and except that a substrate having a thickness of 1,500 μm was prepared by discharging the mixture from the above twin-screw extruder to a T-die having a width of 630 mm and then passing through a chill roll having a temperature of 17°C under the conditions of a screw rotation speed of 40 rpm and a temperature of 200°C.
[0119] Comparative Example 11
[0120] A first separation membrane and a second separation membrane were prepared in the same manner as in the above Example 1, except that 20 parts by weight of ultra high molecular weight polyethylene (UHMWPE) having a weight average molecular weight (Mw) of 2,000,000 and a molecular weight distribution (Mw / Mn) of 5 and 80 parts by weight of paraffin oil having a kinematic viscosity of 70 cSt at 40°C were mixed and fed into a twin-screw extruder (inner diameter: 58 mm, L / D = 56), and except that a substrate having a thickness of 1,700 μm was prepared by discharging the mixture from the above twin-screw extruder to a T-die having a width of 630 mm and then passing through a chill roll having a temperature of 17°C under the conditions of a screw rotation speed of 40 rpm and a temperature of 200°C.
[0121] The main control variables of the production method of the separation membrane according to the above-described examples and comparative examples are shown in Table 2 below. In Table 2 below, Mb and Tb are the draw ratios of the above-described base sheet in the longitudinal direction (MD) and the transverse direction (TD), respectively, and Tc is the draw ratio of the above-described porous membrane in the transverse direction (TD).
[0122] Table 2
[0123]
[0124] Experimental Example
[0125] The puncture strength of the above-described first separation membrane and the heat shrinkage of the above-described second separation membrane according to the above-described examples and comparative examples were measured by the following methods. If the temperature is not mentioned separately, the measurement was performed at normal temperature (25°C), and the results are shown in Table 3 below.
[0126] - Puncture strength (gf): Using a puncture strength measuring device, a stick was applied to a first separation membrane sample having a size of 100 mm x 50 mm, and the force applied until the sample was punctured was measured.
[0127] - Heat shrinkage (%): A second separation membrane sample having a size of 200 mm x 200 mm was sandwiched between A4 papers, and after being left in a 150°C oven for 1 hour, it was cooled to normal temperature. The longitudinal (MD) and transverse (TD) shrinkage lengths of the sample were measured, and the heat shrinkage was calculated using the following equation.
[0128] Heat shrinkage (%) = {(l3-l4) / l3} x 100
[0129] In the above equation, l3 is the longitudinal or transverse length of the second separation membrane sample before shrinkage, and l4 is the longitudinal or transverse length of the second separation membrane sample after shrinkage.
[0130] Table 3
[0131]
[0132]
[0133] The above-described description of the present application is merely illustrative, and as long as it is understood by those skilled in the art to which the present application pertains that the present application can be easily modified into other specific forms without changing the technical idea or essential characteristics of the present application. Therefore, it should be understood that the above-described examples are merely illustrative in all aspects, but are not limited thereto. For example, each structural component described as a single type can be implemented in a dispersed manner, and similarly, each structural component described in a dispersed manner can be implemented in a combined manner.
[0134] The scope of the present application is represented by the appended claims, and not by the foregoing detailed description, and all modifications or variations of the application derived from the meaning, scope and equivalents of the claims should be interpreted as included within the scope of the present application.
Claims
1. A method for producing a separation membrane, characterized by, comprising: Step (a) of processing a composition containing a polyolefin and a pore former to obtain a substrate; Step (b) of stretching the substrate in the longitudinal direction (MD) and the transverse direction (TD) and removing the pore former to obtain a porous membrane; and Step (c) of stretching the porous membrane in the transverse direction (TD) and heat setting it; The production method of the separation membrane satisfies the following conditions (1) to (3): (1) 7 ≤ Mb ≤ 8, (2) 0 < Mb / Tb < 1, (3) 0 < Mb / (Tb × Tc) < 0.5, In the above (1) to (3), Mb and Tb are the stretching ratios of the substrate in the longitudinal direction (MD) and the transverse direction (TD) in the above step (b), respectively, and Tc is the stretching ratio of the porous membrane in the transverse direction (TD) in the above step (c).
2. The production method of the separation membrane according to claim 1, wherein the weight average molecular weight (Mw) of the polyolefin is 1,000,000 to 4,000,000.
3. The production method of the separation membrane according to claim 2, wherein the polyolefin comprises one selected from the group consisting of polyethylene, polypropylene, polybutylene, polymethylpentene, ethylene vinyl acetate, ethylene butyl acrylate, ethylene ethyl acrylate, and a combination or copolymer of two or more of them.
4. The production method of the separation membrane according to claim 1, wherein the Tc is 1.5 to 2.
0.
5. The production method of the separation membrane according to claim 1, wherein the ratio of Mb to Tc (Mb / Tc) is 3.0 to 5.
0.
6. The production method of the separation membrane according to claim 1, wherein the pore former is paraffin oil having a kinematic viscosity of 50 cSt to 100 cSt at 40°C, respectively.
7. The production method of the separation membrane according to claim 1, wherein the thickness of the substrate obtained in the above step (a) is 1000 μm to 1500 μm, the thickness of the porous membrane obtained in the above step (c) is 10 μm or less, and the puncture strength is 500 gf or more. After the above step (c), a step (d) of applying a coating solution containing a binder and a solvent to at least one side of the porous membrane and drying it to form a functional layer is further included.
9. The production method of the separation membrane according to claim 8, wherein the binder contained in the coating solution is a water-soluble polymer. 8. The method for producing a separation membrane according to claim 1, characterized by, The above-mentioned adhesive is one selected from the group consisting of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride-trichloroethylene, polymethyl methacrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinyl acetate, ethylene vinyl acetate, polyimide, polyethylene oxide, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, hydroxyethyl cellulose, cyanoethyl sucrose, pullulan, carboxymethyl cellulose, polyvinyl alcohol, polyvinyl butyral, acrylonitrile-acrylic acid copolymer, ethylene-acrylic acid copolymer, styrene-butadiene copolymer, alkyl acrylate-acrylonitrile copolymer, polyethylene glycol, acrylic rubber, and a combination of two or more thereof.
10. The method for producing a separation membrane according to claim 8, characterized in that The above-mentioned solvent is one selected from the group consisting of methanol, ethanol, propanol, butanol, methoxyethanol, ethoxyethanol, lactone, acetonitrile, n-methyl-2-pyrrolidone, formic acid, nitromethane, acetic acid, dimethyl sulfoxide, water, and a combination of two or more thereof.
11. The method for producing a separation membrane according to claim 8, characterized in that The above-mentioned coating solution further includes one inorganic particle selected from the group consisting of SiO2, AlO(OH), Mg(OH)2, Al(OH)3, TiO2, BaTiO3, Li2O, LiF, LiOH, Li3N, BaO, Na2O, Li2CO3, CaCO3, LiAlO2, Al2O3, SiO, SnO, SnO2, PbO2, ZnO, P2O5, CuO, MoO, V2O5, B2O3, Si3N4, CeO2, Mn3O4, Sn2P2O7, Sn2B2O5, Sn2BPO6, and a combination of two or more thereof.
12. A separation membrane, the separation membrane being one produced by the method for producing a separation membrane according to any one of claims 8 to 11, the separation membrane being characterized by satisfying the following conditions (i) to (iii): (i) a longitudinal (MD) heat shrinkage at 150°C is 5% or less, (ii) a transverse (TD) heat shrinkage at 150°C is 5% or less, (iii) a ratio of the transverse (TD) heat shrinkage to the longitudinal (MD) heat shrinkage at 150°C is 1.1 or less.
Citation Information
Patent Citations
Microporous polyethylene film and production thereof
JP1985242035A